Pengaruh Pajak Hotel dan Pajak Restoran terhadap Pendapatan Asli Daerah (PAD) Kota Jambi Tahun 2013–2024 - Setyo Adi Laksono (Lembaga Yasin AlSys, 2025)
The importance of hotel and restaurant taxes as primary sources of Regional Original Revenue (PAD) forms the background of this study, particularly in Jambi City, which has experienced growth in the tourism and service sectors but continues to face a gap between tax potential and actual revenue. This study aims to analyze the effect of hotel and restaurant taxes on Jambi City's PAD during the 2013–2024 period. A quantitative approach was employed using multiple linear regression analysis with EViews software. The data analyzed consisted of quarterly secondary data on hotel tax, restaurant tax, and PAD revenue obtained from the Regional Tax and Retribution Management Agency (BPPRD) of Jambi City, using a saturated sampling technique covering the entire observation period. Model validity was tested through classical assumption tests, t-tests, F-tests, and the coefficient of determination (R²). The results indicate that hotel tax has a positive and significant effect on PAD, while restaurant tax does not have a statistically significant partial effect. However, jointly, both taxes have a significant effect on PAD, contributing 39% to its variation. The study concludes that hotel tax is a strategic instrument for increasing Jambi City's PAD and should be optimized through tax base expansion, tourism sector promotion, and improved taxpayer compliance. In contrast, the effectiveness of restaurant tax requires further evaluation of its collection mechanisms to enhance its contribution to PAD.